Development of Digital Infrastructure and Increasing Productivity of MSMEs to Encourage Competitiveness in the Digital Era - Zahra Salsa Bella; Rhandi Rhiswandi (Journal Tourism Nomic, 2025)
Micro, small and medium enterprises constitute a fundamental pillar of Indonesia’s economic development and sustainability, especially in job creation and local industrial growth. However, the main challenge faced by MSMEs in increasing their competitiveness is access to digital infrastructure that is still limited. This study analyzes the impact of digital infrastructure development on the productivity of MSMEs as well as strategies that can be applied to increase the adoption of digital technology. This study refers to various previous studies that show that the adoption of digital technology, such as e-commerce and digital payment systems, is able to improve operational efficiency and expand market access for MSMEs (Badriyah et al., 2022). The study result indicated that the success of MSMEs in utilizing digital infrastructure is highly dependent on access to a stable internet, policy support, and increased digital literacy (Lukas & Hasudungan, 2024). Partnership between goverment, private sector and the business community in building digital infrastructure and providing training is crucial in accelerating the digital transformation of MSMEs Kumar et al. (2024). This study recommends accelerating the development of internet networks in remote areas, providing incentives for MSMEs that adopt digital technology, and implementing digital skills improvement programs for business actors. With a strong digital ecosystem, MSMEs can be more competitive and sustainable in facing the challenges of the digital economy.